Teachers as Drivers of Innovation: Optimizing Project-Based Learning for Students - Maknunah, Farhatul (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to analyze the role of teachers in encouraging student innovation through the application of project-based learning methods at the junior high school level. Using a descriptive qualitative approach, this study examines how teachers function as facilitators, mentors, motivators, and evaluators during the learning process. The results show that the role of teachers has a significant impact in developing students' creativity, critical thinking skills and innovation. Through the project- based learning method, teachers not only direct students in completing tasks, but also create a learning environment that supports the exploration of ideas, collaboration, and the application of knowledge in a real context. Thus, this research highlights the importance of teachers' active role in creating an innovative learning atmosphere and empowering students to think creatively and critically.